Representing Gender in Chinese Children’s Literature (1920 – 2010) - Bi, Lijun; Fang, Xiangshu (SARE: Southeast Asian Review of English, 2018)
This study investigates the representation of gender roles in Chinese children’s literature from 1920 to 2010, focusing on constructions of masculinity and femininity in different historical contexts. The paper attempts to demonstrate the persistence of, as well as departures from, traditional stereotypes about gender roles in China throughout the last century. Although there is no definite evidence that children’s literature is a deciding factor in the assigning of gender roles to the young in China, the influence of literary works on how gender is perceived and constructed in society cannot be denied. A close reading of these literary texts offers us insights into understanding the changing representation of gender roles in Chinese children’s literature, which reflect changes in society and social attitudes toward gender in mainland China.